Impact of increased predation risk on vigilance behaviour in a gregarious waterfowl, the Egyptian goose Alopochen aegyptiaca. (12th June 2019) - Atkins, Alex; Little, Rob M.; Redpath, Stephen M.; Amar, Arjun
Abstract : Vigilance is amongst the most universal of anti‐predator strategies and commonly declines with increasing group size. We experimentally manipulated predation risk in a system with a known relationship between group size and vigilance levels to explore whether this relationship changes in response to elevated predation risk. We investigated the vigilance levels of Egyptian geese Alopochen aegyptiaca at eight golf courses in the western Cape, South Africa, to assess the perception of and reaction to predation risk. We manipulated predation risk by introducing trained Harris's hawks Parabuteo unicintus where avian predation was otherwise low or absent. The study confirmed the typical reduction in vigilance with group size on control sites, where the risk of predation is low. However, at experimental sites with elevated predation risk, a positive relationship between vigilance and group size was observed. We hypothesize that the mechanism for this relationship might be linked to social information transfer via copying behaviour and manipulation to induce vigilance. Thus, larger groups will have a higher probability of containing individuals with experience of elevated predation risk and their increased vigilance behaviour is copied by naïve individuals. This prediction is based on the intended outcome of introducing avian predation to make the geese feel less safe and to eventually leave the site as a management tool for controlling nuisance geese.